2005
DOI: 10.1158/0008-5472.can-05-1201
|View full text |Cite
|
Sign up to set email alerts
|

Myxoma Virus Is a Novel Oncolytic Virus with Significant Antitumor Activity against Experimental Human Gliomas

Abstract: Myxoma virus, a poxvirus previously considered rabbit specific, can replicate productively in a variety of human tumor cells in culture. The purpose of this study was to determine if there was efficacy or toxicities of this oncolytic virus against experimental models of human malignant gliomas in vitro, in vivo, and ex vivo in malignant glioma specimens. In vitro, the majority of glioma cell lines tested (7 of 8, 87.5%) were fully permissive for myxoma virus replication and killed by infection. In vivo, intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
168
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(176 citation statements)
references
References 39 publications
1
168
1
6
Order By: Relevance
“…20 Myxoma virus, a rabbit poxvirus with a similar restricted tropism, functions as an oncolytic virus in human tumor cells bearing deficiencies in type I IFN and tumor necrosis factor-a (TNFa) pathways. 23,24 Before investigating the oncolytic capacity of BHV-1, we first confirmed the restriction of normal human cells against BHV-1 replication and CPE induction. A panel of six non-immortalized, non-transformed cell types (refer to Table 1 for cell type information) were infected with increasing amounts of BHV-1, and CPE was monitored 3 days post-infection.…”
Section: Bhv-1 Replication Is Restricted In Normal Human Cellsmentioning
confidence: 93%
“…20 Myxoma virus, a rabbit poxvirus with a similar restricted tropism, functions as an oncolytic virus in human tumor cells bearing deficiencies in type I IFN and tumor necrosis factor-a (TNFa) pathways. 23,24 Before investigating the oncolytic capacity of BHV-1, we first confirmed the restriction of normal human cells against BHV-1 replication and CPE induction. A panel of six non-immortalized, non-transformed cell types (refer to Table 1 for cell type information) were infected with increasing amounts of BHV-1, and CPE was monitored 3 days post-infection.…”
Section: Bhv-1 Replication Is Restricted In Normal Human Cellsmentioning
confidence: 93%
“…A recent report has indicated that this virus exhibits a natural tropism for many human tumor cells [93], indicating that this virus could be used as a therapy in cancer treatment. Studies in a mouse model of glioma has shown that this virus is quite effective in infecting tumor tissue in vivo and effectively 'cured' mice from these brain tumors [56]. These studies have fostered enthusiasm in the prospect of using this virus clinically to treat human cancers [66].…”
Section: Prevention Control and Vaccinationmentioning
confidence: 99%
“…In gene therapy approaches, a therapeutic gene for mutation compensation, immunopotentiation, or prodrug activation is transferred. [2][3][4][5][6][7] In virotherapy, tumor cell killing is achieved by oncolysis; that is, virus replication induced cell killing. [8][9][10] Both of these therapeutic interventions allow for specific antitumor effects via molecular targeting strategies that exploit tumor markers.…”
Section: Introductionmentioning
confidence: 99%